PENGARUH FOO (SAMPAH) DI SISI UDARA TERHADAP KESELAMATAN DAN KEAMANAN PENERBANGAN DI BANDAR UDARA KALIMARAU BERAU KALIMANTAN TIMUR - Ade Putra Akbar; Ahmad Musadek; Fatimah (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
This Final Project research with the title "the effect of Foreign Object Damage at Air Side on aviation safety and security' the purpose of this study is, to determine and test that, the accumulation of garbage in Air Side has an effect on aviation safety and security, as well as to improve safety, and aviation security. The author uses descriptive quantitative research methods , with data collection techniques in the form of observation, literature study, distributing questionnaires to Apron Movement Control and Ground Handling personnel and conducting interviews with Apron Movement Control personnel. The author chooses a quantitative descriptive research method because the results obtained are in the form of numbers and are clear so that the author can use the Likert Scale research instrument to get the results of the research that has been done, by calculating each one of the statements, then ranked using the Spearman Rank formula, and conclude the results of the interview answers that the author has done. The results of the discussion "the effect of garbage accumulation at Air Side on aviation safety and security' the authors get the results that the accumulation of garbage at Ground Support Equipment affects the safety and security of flights. Temporary garbage storage places that are not in accordance with the regulations, and the use of the Ground Support Equipment (Baggage cart) facility as a place to transport garbage results that it affects aviation safety and security. The conclusion of this study is that garbage in the Air Side disturbs aviation safety and security so that supporting facilities for cleanliness are needed, so that flight services at Kalimarau Berau Airport can run smoothly.